Strategi Pembiayaan pada Lembaga Pendidikan Islam melalui Tanggung Jawab Sosial (SCR) Studi Kasus BANK BRI Syariah - Yayuk Purwati (Lembaga Penelitian, Penerbitan dan Pengabdian (LP3M) IAI Al-Urwatul Wutsqo Jombang, 2021)
Social responsibility or Corporate Social Responsibility is not only to complement obligations based on law and morals, but it is also present as a strategy for society and the company to survive for a long time. If this Social Responsibility is eliminated it will have an impact on the company, one of which will bear a lot of financing. But if on the other hand the company carries out its Social Responsibility properly, including ensuring the distribution of financing fairly and correctly, then this will later lead to benefits in a long period of time for the company. BRI Syariah in carrying out CSR in the field of education provides a program called Education Benefits which aims to support the quality of education in the community. In 2018 the Company has carried out around 33 activities including: providing scholarship financing to outstanding students who are categorized as poor students in 9 universities, then providing scholarships to children of BRI Syariah employees who are ordinary workers, Providing financing assistance for renovation of madrasah and early childhood education in Bogor, Palangkaraya and Lebak Banten and held SIMPEL (Simpanan Pelajar) activities throughout Indonesia. In 2017 BRI Syariah collaborated with Baznas to hold a Santripreneur Program namely Quail Cultivation, Then there is also one university that collaborates with BRI Syariah, namely UIN Walisongo Semarang which on February 24 2020 entered into a memorandum of understanding or (MoU).